The fate of aerobic heterotrophic bacteria single-cell protein production under differnet C/N ratios - Lau, Hiu Naam (Nanyang Technological University, 2024)
Aerobic heterotrophic bacteria represent an upcoming source of alternative protein for animal feed. Carbon-to-nitrogen (C/N) ratio are known to affect the composition microbial community, in turn the performance of the bioreactor. This study investigated two C/N ratios, 100:1 and 100:3.5 and their impact on the single cell protein (SCP) production. The higher C/N ratio produced better results, with biomass yield reaching 0.735 g/g COD and amino acid content of 41.20 mg/mg%. Removal rates of 97.73% and 100% was chieved for chemical oxygen demand and ammonium respectively. Various microbial genera such as Lysobacter, Rhodobacter and Prevotella_9 identified within the bioreactor.